Preservation of orbit in tumor invasion through the periorbita in sinonasal malignancy - Novak, Stepan; Balatkova, Zuzana; Fikova, Alzbeta; Grega, Marek; Kalfert, David; Plzak, Jan (European archives of oto-rhino-laryngology, 2024)
OBJECTIVE: One of the possible risks of sinonasal malignancy is its possible spread in the orbit. However, there is no clear consensus among the different departments as to whether it is necessary to exenterate the orbit in limited tumorous infiltration of periorbital fat. The purpose of the study was to demonstrate that periorbital infiltration and periorbital fat invasion without involvement of deeper orbital tissues are not the indication of orbital exenteration. MATERIALS AND METHODS: Retrospective analysis was performed over a 17-year period of patients undergoing surgical treatment for sinonasal malignancy with histologically verified periorbital infiltration or deeper invasion into the orbit. A total of 32 patients were included in the study. For each group, the following data were analysed: sex, age, preoperative imaging studies, histological findings, site of origin, stage, surgical reconstruction, oncological treatment, survival, cause of death, number of recurrences in the orbit and functional status of preserved eyes. RESULTS: Based on our criteria for orbital exenteration, orbital preservation was feasible in 18 patients. Orbital exenteration was performed in 14 patients with deeper tumor infiltration. There was a statistically insignificant difference in survival between the two groups. The 5-year overall survival (OS) was 44% for the orbital preservation group (only 2 patients died from local tumor recurrence) and 34% for the orbital exenteration group. The groups did not differ in other observed factors other than the extent of orbital infiltration. In 11 (61.1%) patients, vision was without significant change after radiation therapy. In 2 (11.1%) patients, visual function was impaired due to diplopia. 5 (27.8%) patients had severely impaired vision due to optic nerve atrophy after radiation therapy. CONCLUSIONS: Our results show a relatively high survival rate in the group of patients with orbital preservation with a high chance of vision preservation, which justifies our approach to orbital preservation even in some tumors with periorbital infiltration.
Keywords: Male; Orbital Neoplasms; retrospektivní studie; Organ Sparing Treatments; Neoplasm Staging; eviscerace orbity; Neoplasm Invasiveness; Adult; Paranasal Sinus Neoplasms; Aged; dospělí; mužské pohlaví; senioři; nádory vedlejších dutin nosních; Orbit; Periorbital infiltration; Vision; nádory orbity; Orbit Evisceration; senioři nad 80 let; lidé; ženské pohlaví; Humans; invazivní růst nádoru; Aged, 80 and over; léčba šetřící orgány; orbita; Orbital exenteration; Retrospective Studies; Female; lidé středního věku; staging nádorů; Sinonasal malignancy; Orbital preservation; Survival; Middle Aged